Association between marital status and cognitive impairment based on a cross‐sectional study in China. (9th November 2021) - Chen, Zhi‐Chao; Wu, Hao; Wang, Xiao‐Dan; Zeng, Yan; Huang, Guowei; Lv, Yang; Niu, Jianping; Meng, Xinling; Cai, Pan; Shen, Lu; Gang, Baozhi; You, Yong; et al.
Abstract: Background: Marital status may have an impact on the elderly population's health, but few studies in China discussed about the association between marital status and cognitive impairment. Objective: To investigate the relationship between marital status and cognitive impairment. To compare the influences of marital status on dementia between men and women. Methods: This study was based on a representative national cross‐sectional epidemiological survey in China. We randomly selected 13 provinces and municipalities and included 19, 276 participants aged 65 years or older in our study. Data was collected by interviewing the participants about their sociodemographic characteristics, and neuropsychological testing was administered to the participants by neurologists. To analyze the association between marital status and cognitive impairment, multiple logistic regression was based on a series of models. Results: Among the 19, 276 subjects, about 77.2% were married, 1.6% were single, 21.2% were divorced/separated or widowed. The odds ratios (OR) of dementia were higher in single (OR: 2.13, CI: 1.53–2.97; p  < 0.001), divorced/separated/widowed when they were ≤55 years old (OR: 1.75, CI: 1.30–2.35; p  < 0.001), and divorced/separated/widowed when they were >55 years old (OR: 1.16, CI: 1.03–1.31; p  < 0.001) participants than in married ones. Divorced/separated/widowed ≤55 men had about 2.75 times increase in dementia risk than married men. Conclusion: People with long‐term divorced/separated/widowed status would be associated to cognitive impairment more than those with short‐term divorced/separated/widowed status. Men may be affected by marriage disruption more than women in terms of increasing the risk of dementia. Key points: People divorced/separated/widowed ≤55 would be associated to cognitive impairment more than those divorced/separated/widowed >55 years old Men may be affected by marriage disruption more than women in terms of increasing the risk of dementia